Anti-RBD IgG antibodies from endemic coronaviruses do not protect against the acquisition of SARS-CoV-2 infection among exposed uninfected individuals - Adami, Flávia Lopes; de Castro, Mateus Vidigal; Almeida, Bianca da Silva; Daher, Isabela Pazotti; Yamamoto, Márcio Massao; Souza Santos, Keity; Zatz, Mayana; Naslavsky, Michel Satya; Rosa, Daniela Santoro; Cunha-Neto, Edecio; de Oliveira, Vivian Leite; Kalil, Jorge; et al. (Frontiers in Immunology, 2024)
The Coronaviridae family comprises seven viruses known to infect humans, classified into alphacoronaviruses (HCoV-229E and HCoV-NL63) and betacoronaviruses (HCoV-OC43 and HCoV-HKU1), which are considered endemic. Additionally, it includes SARS-CoV (severe acute respiratory syndrome), MERS-CoV (Middle East respiratory syndrome), and the novel coronavirus SARS-CoV-2, responsible for COVID-19. SARS-CoV-2 induces severe respiratory complications, particularly in the elderly, immunocompromised individuals and those with underlying diseases. An essential question since the onset of the COVID-19 pandemic has been to determine whether prior exposure to seasonal coronaviruses influences immunity or protection against SARS-CoV-2. In this study, we investigated a cohort of 47 couples (N=94), where one partner tested positive for SARS-CoV-2 infection via real-time PCR while the other remained negative. Plasma samples, collected at least 30 days post-PCR reaction, were assessed using indirect ELISA and competition assays to measure specific antibodies against the receptor-binding domain (RBD) portion of the Spike (S) protein from SARS-CoV-2, HCoV-229E, HCoV-NL63, HCoV-OC43, and HCoV-HKU1. IgG antibody levels against the four endemic coronavirus RBD proteins were similar between the PCR-positive and PCR-negative individuals, suggesting that IgG against endemic coronavirus RBD regions was not associated with protection from infection. Moreover, we found no significant IgG antibody cross-reactivity between endemic coronaviruses and SARS-CoV-2 RBDs. Taken together, results suggest that anti-RBD antibodies induced by a previous infection with endemic HCoVs do not protect against acquisition of COVID-19 among exposed uninfected individuals.